Networked business models in the circular economy - Nogalski, Bogdan (Advances in finance, accounting, and economics (AFAE) book series., 2020)
"This book develops and presents the assumptions of business model in sharing and circular economy as a key determinant of the performance of the company embedded in the network. It also explores the relationship between the business model in sharing and circular economy and achieving company performance in a network environment"--